F(x)=x2-26x+144

Simple and best practice solution for F(x)=x2-26x+144 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(x)=x2-26x+144 equation:



(F)=F2-26F+144
We move all terms to the left:
(F)-(F2-26F+144)=0
We add all the numbers together, and all the variables
-(+F^2-26F+144)+F=0
We get rid of parentheses
-F^2+26F+F-144=0
We add all the numbers together, and all the variables
-1F^2+27F-144=0
a = -1; b = 27; c = -144;
Δ = b2-4ac
Δ = 272-4·(-1)·(-144)
Δ = 153
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{153}=\sqrt{9*17}=\sqrt{9}*\sqrt{17}=3\sqrt{17}$
$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(27)-3\sqrt{17}}{2*-1}=\frac{-27-3\sqrt{17}}{-2} $
$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(27)+3\sqrt{17}}{2*-1}=\frac{-27+3\sqrt{17}}{-2} $

See similar equations:

| 3x+6-4=16+5x= | | -35=-(5/7)h | | -7(1+2m)=-91 | | 15=4t+5 | | a-25=(5.30)+12 | | 3x+6-4=16+5x+ | | x-12+5x+32=50 | | -4n+11.5=-1/ | | -17=x+(-4) | | -3/4x+11=20 | | 6(1+3v)=-84 | | 25p-25=10p+200= | | 3x+5(x+1)=7.1+5.3(3x+2) | | 2=2+x/4 | | 2x-28=(1/2)3x-40 | | 2^(x-3)=256 | | b-17=-19 | | 2*x+11=7 | | 8y-(5²+2²)=3= | | 2n+8+2n=48 | | -7b-8(b=4)=88 | | n+n1/5=24 | | 3x-5x+1=(2x-1) | | 3x-5=-6+1 | | -12p=3p | | 3x-5=-7+1 | | 3x-5=-5+1 | | 3x-5=-2+1 | | x/2+4=−1 | | 6^2=-36x | | 5x-2x=5+4 | | 3x-5=-1+1 |

Equations solver categories